Holistic Health: Does It Really Include Mental Health? - Kimberly K. McClanahan; Marlene B. Huff; Hatim A. Omar (The Scientific World Journal, 2006)
Holistic health, incorporating mind and body as equally important and unified components of health, is a concept utilized in some health care arenas in the United States (U.S.) over the past 30 years. However, in the U.S., mental health is not seen as conceptually integral to physical health and, thus, holistic health cannot be realized until the historical concept of mind-body dualism, continuing stigma regarding mental illness, lack of mental health parity in insurance, and inaccurate public perceptions regarding mental illness are adequately addressed and resolved. Until then, mental and physical health will continue to be viewed as disparate entities rather than parts of a unified whole. We conclude that the U.S. currently does not generally incorporate the tenets of holistic health in its view of the mental and physical health of its citizens, and provide some suggestions for changing that viewpoint.